INTERFERENSI BAHASA MOI TERHADAP STRUKTUR KALIMAT BAHASA INDONESIA DI PAPUA BARAT - Mecca Ardelia; Qonita Tillah; Agni Aulia; Redika Cindra Reranta (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study examines the syntactic interference of the Moi language with Indonesian in West Papua. The goal is to identify forms of sentence structure deviations that arise due to the influence of the Moi grammatical system. Using qualitative descriptive methods and contrastive analysis, data were collected from Moi speakers' speech in various communication contexts. The results indicate interference in word order (S–O–P), nominal phrase structure (N–Num), and the placement of adverbs and negations that differ from standard Indonesian. This phenomenon illustrates the transfer of patterns from Moi, which has a distinctive structure and places verbs at the end of clauses. In general, this interference is not simply a linguistic error, but rather a form of syntactic adaptation in bilingual situations that forms a local variant of Indonesian with a Moi accent.